Perlindungan Hak Mewaris Seorang Anak Hasil Perkawinan Ijab Qabul Tidak Tercatat pada Hukum Negara (Lex Jurnalica, 2010)
Based on the foregoing with generally accepted theories, it is to argue that a private covenant of marriage is valid according to it’s religion and it is government’s responsibility for providing legal protection.  Therefore, any child born from private covenant of marriage is a legitimate child and shall therefore be entitled to legal protection by government through court’s decision (yurisprudensi) that provide inherated right to child from private covenant of marriage.Keywords: Marriage, Law Protection, Inheritance